The Value of Companion Dogs as a Source of Social Support for Their Owners: Findings From a Pre-pandemic Representative Sample and a Convenience Sample Obtained During the COVID-19 Lockdown in Spain - Bowen, Jonathan; Bulbena, Antonio; Fatjó, Jaume (Frontiers in Psychiatry, 2021)
Dogs are a source of companionship and comfort for their owners, but the degree to which this might translate into real emotional and social support has not been quantified. Emotional and social support are essential to help people to get through personal crises such as bereavement. In this study we characterize the social support owners obtain from their dogs, provide evidence of how widespread this social support is amongst dog-owners, and show how social support from dogs can increase during a crisis (using the COVID-19 pandemic as an example). We collected data from a representative population-based sample of Spanish dog-owners and found that most respondents said that their dogs helped them to get through tough times. They got comfort from physical contact with their dogs, shared activities with them and treated them as confidants in a similar way to friends and family. These are all key aspects of social support, and dogs offer the advantage of being more available than human sources of support. It would be expected that the support that dogs provide would be increased during a time of personal crisis and when we looked at data collected from a convenience sample of Spanish dog-owners during the COVID-19 confinement that is what we found; during the confinement owners engaged in more shared activities with their dogs, hugged them more often and turned to them more as a source of companionship and comfort (p < 0.0001 in all cases). However, although owners did confide more in their dogs (p < 0.0001), the effect was not as great as for other aspects of social support. We suspect that this is because people were able to use telecommunications such as video conferencing to maintain their human confidant relationships. Our findings indicate that dogs can substitute for humans as sources of some kinds of social support when conventional sources are unavailable. Our conclusion is that where a dog is present in a household, it should be regarded as an important resource for social support. This should be considered when designing clinical interventions and when public health decisions are being made.